Multiplex Quantification of Plasma Biomarkers for Patients with Gaucher Disease Type 1. Issue 2 (21st February 2023) - Menkovic, Iskren; Boutin, Michel; Lavoie, Pamela; Auray‐Blais, Christiane
Abstract: Gaucher disease (GD) is a lysosomal storage disorder caused by a deficiency of the enzyme beta‐glucocerebrosidase. This leads to the accumulation of glycolipids in macrophages and ultimately results in tissue damage. Recent metabolomic studies highlighted several potential biomarkers in plasma specimens. In hopes of better understanding the distribution, importance, and clinical significance of these potential markers, a UPLC‐MS/MS method was developed and validated to quantify lyso‐Gb1 and six related analogs (with the following modifications on the sphingosine moiety: ‐C2 H4 (‐28 Da), ‐C2 H4 +O (‐12 Da), ‐H2 (‐2 Da), ‐H2 +O (+14 Da), +O (+16 Da), and +H2 O (+18 Da)), sphingosylphosphorylcholine, and N‐ palmitoyl‐O‐phosphocholineserine in plasma specimens of treated and untreated patients. This 12‐min UPLC‐MS/MS method involves a purification step via solid‐phase extraction followed by evaporation under nitrogen flow and resuspension in an organic mix compatible with HILIC chromatography. This method is currently used for research purposes and might be used for monitoring, prognostics, and follow‐up. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC.